Determination of the vibrating table kinetic energy - Korobko, Bogdan; Zhyhylii, Serhii; Korotych, Yuriy (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article determines the total kinetic energy of the vibrating table, in which the vibrator is fixed on a lever vertically in the center under the vibrating plate. To find the total kinetic energy, a kinematic diagram of the vibrating table under study was drawn up, and the functional dependence of the vibrating table total kinetic energy on the factors acting on it obtained. A graph of the change in the vibrating table kinetic energy under study was drawn depending on the lever length, on which the vibrator was fixed. The analysis of the resulting dependence indicates an increase in the kinematic energy of the vibrating table with an increase in the lever length. The obtained kinetic energy is necessary for the development of an above-mentioned equipment mathematical model, which will be compiled later using Lagrange equations of the second kind
Keywords: vibrating table; lever; vibrator; imbalance; degree of freedom; kinetic energy